Program CSR PT BANK RAKYAT INDONESIA, TBK Dalam Memperbaiki Kualitas Lingkungan Hidup Indonesia - Syarief, Fauzi (LPPM Universitas Bina Sarana Informatika, 2020)
This research is a research on how to use SWOT analysis in an organization's Corporate Social Responsibility strategy. The formulation of the problem in this study is